Elastic Optical Networks Architectures, Technologies, and Control - López, Víctor; Velasco, Luis.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book addresses challenges and potential solutions surrounding the dramatic yearly increases in bandwidth demand. The editors discuss the predicament surrounding current growth, which is predicted to continue because of the proliferation of disruptive, high bandwidth applications like video and cloud applications. They also discuss that in addition to growth, traffic will become much more dynamic, both in time and direction. The contributors show how large changes in traffic magnitude during a 24-hour period can be observed, as day-time business users have very different demands to evening-time residential customers, and how this plays into addressing future challenges. In addition, they discuss potential solutions for the issues surrounding situations where multiple content and cloud service providers offer competing services, causing the traffic direction to become more dynamic. The contributors discuss that although the WDM transponder technology can be upgraded to 100Gb/s inthe short to medium term, and to 1Tb/s in the longer term, bandwidth-variable transponders that can adjust their bandwidth quickly and under software control are needed. In addition, they posit that by using a flexible grid the optical spectrum can be used in a more flexible way. The book comprehensively addresses all these topics and aims at providing a reference for the coming years for researchers, engineers, and practitioners working in the field. Planning and algorithms for elastic optical networks (EONs) are presented, including mathematical models and algorithms. Discusses the evolution from WDM to flexible and the new applications that EONs can support Shows how in the data plane, transmission in EON will cover the next generation of bandwidth variable transponders, novel modulation formats, mitigation of impairments, and node architectures Presents extensions to GMPLs and OpenFlow for EONS in the control plane, extensions to GMPLS and OpenFlow for EONs, and the concept of in-operation planning.
Introduction -- Part I Network Architecture and Planning. - Evolution from Wavelength Switch to Flexgrid Optical Networks -- Taking Advantage of Elastic Optical Networks -- Routing and Spectrum Allocation -- Part II Data Plane -- Transmission in Elastic Optical Networks -- Node Architecture -- Sliceable Bandwidth Variable Transponders -- Part III Control Plane -- Control Plane Architecture -- OpenFlow in Optical Networks -- Application Based Network Operations -- In-operation Planning. Architecture and Use Cases -- Conclusion.
Keywords: Telecommunication; Computer networks .; Communications Engineering, Networks; Microwaves, RF Engineering and Optical Communications; Computer Communication Networks